2020
DOI: 10.5713/ajas.19.0596
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable discards preserved with sodium metabisulfite as a high-moisture ingredient in total mixed ration for ruminants: effect on in vitro ruminal fermentation and in vivo metabolism

Abstract: Objective: Our recent series of laboratory- and large-scale experiments confirmed that under aerobic and anaerobic conditions, sodium metabisulfite (SMB) was effective in preserving nutrients and antioxidant capacity of highly perishable fruit and vegetable discards (FVD). Hence, the purpose of this study was to examine how partial inclusion of SMB-treated FVD in total mixed ration (TMR) influences in vitro ruminal fermentation, whole-tract digestibility, nitrogen metabolism, blood metabolites, and voluntary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…During the 80-d collection period, DM, CP, and WSC contents ranged from 12.8 to 15.8%, from 6.1 to 8.9% of DM, and from 37.9 to 50.3% of DM, respectively. These values are consistent with those obtained in our laboratory over a 3-yr period, indicating that FVD biomass is high in soluble sugars and moisture but low in fiber and protein contents [3,4,6,7]. Our previous observations confirmed that these FVD biomass characteristics accelerated putrefaction by active microbial populations.…”
Section: Fvd Preparation and Diet Characteristicssupporting
confidence: 90%
See 3 more Smart Citations
“…During the 80-d collection period, DM, CP, and WSC contents ranged from 12.8 to 15.8%, from 6.1 to 8.9% of DM, and from 37.9 to 50.3% of DM, respectively. These values are consistent with those obtained in our laboratory over a 3-yr period, indicating that FVD biomass is high in soluble sugars and moisture but low in fiber and protein contents [3,4,6,7]. Our previous observations confirmed that these FVD biomass characteristics accelerated putrefaction by active microbial populations.…”
Section: Fvd Preparation and Diet Characteristicssupporting
confidence: 90%
“…Based on the moisture and energy content similarities between FVD (an estimated average TDN of 80.2% and moisture content ranging from 85 to 88% [3,4,6,7]) and WBG, we hypothesized that FVD could be used as a replacement of WBG in the rations of Hanwoo heifers and cows.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 2 more Smart Citations
“…Because the pineapple by-products generally contain high water-soluble and moisture contents like other fruit by-products, they have the potential to readily decay [ 15 ]. Although there are certain procedures for decreasing the moisture content of PCB, such as sun-drying or artificial drying, sun-drying is impracticable during the rainy season and artificial drying generates additional expenses and it also requires special facilities.…”
Section: Discussionmentioning
confidence: 99%